Analisis Pengelolaan Dana Bantuan Operasional Sekolah Daerah (BOSDA) Dan Bantuan Operasional Sekolah Nasional (BOSNAS) Tingkat Sekolah Menengah Atas Negeri Kota Samarinda Terhadap Kinerja Keuangan Sekolah. (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2020)
This study aims to know and to do the implementation of local and national government fund program towards the performance of senior high school city level in samarinda has been running with applicable regulation or not and also to find out the financial management in this case the expenditure.            This research is about 18 senior high school level in Samarinda City.In this study using descriptive research with a quantitative approach. This study shows the results that the Implementation of the National School Operational Assistance Program (BOSNAS) and Regional Middle School Operational Assistance (BOSDA) in Samarinda City have met the stipulated regulations. Financial management in this case is the expenditure / realization of the National School Operational Assistance Program (BOSNAS) and Regional Operational Assistance (BOSDA) impacting the performance of State High Schools in Samarinda City.Funds allocated for 18 schools in Samarinda city sourced from BOSNAS and BOSDA amounted to Rp. 27. 917,500,000 while the realization was Rp. 24,586,745,984 or 88%. Funds that cannot be used are Rp. 3,330,754,016 (22%), this amount, if it can be utilized optimally, will certainly further increase the benefits of BOS budgeting objectives, namely to improve the quality of education services, especially those directly related to teachers, education staff, administrative staff and students school.